Influence of characteristic material properties on machinability under high speed cutting. (10th March 2009) - Brinksmeier, Ekkard; Walter, Andre; Reucher, Griet; Solter, Jens
New tool materials, high performance spindle systems and intelligent driving systems make possible a drastic increase in the cutting speed for machine tools. High Speed Cutting (HSC) can lead to enhanced surface qualities and lower cutting forces. With a view to the state of the art, it can be pointed out that the scientific basics of HSC are not well-known. Therefore, the aim of this presented investigation was to determine the influence of different mechanical, thermal and structural workpiece material properties on chip formation mechanism under HSC conditions. The results show that for certain materials, a significant decrease of the resultant force with increasing cutting speed exists. Machining of high precision component parts with high cutting speeds should be favourable since lower process forces should lead to a reduction of elastic workpiece deformation during machining.